The ESG disclosure and the financial performance of Norwegian listed firms - Geōrgios A. Giannopulos; Renate Victoria Kihle Fagernes; Mahmoud Elmarzouky; Kazi Abul Bashar Muhammad Afzal Hossain (Journal of Risk and Financial Management, 2022)
The world is constantly changing, and with an evolving global environmental crisis, there is a growing trend of Corporate Social Responsibility, and Environmental, Social, and Governance (ESG) disclosure initiatives. The final report on the new E.U. taxonomy for sustainable activities was released in 2020, making ESG disclosure more relevant. This paper investigates the effects of ESG initiatives on the financial performance of Norwegian listed companies from 2010 to 2019. ESG is measured through the Thomson Reuters Eikon ESG disclosure score and financial performance through ROA and Tobin's Q. To the best of our knowledge, this is the first time this relationship has been investigated in Norway. Using panel data regression analysis and two proxies for the dependent variable (financial performance), the results of this study are mixed. In particular, findings suggest a strong significant relationship between ESG initiatives and financial performance. More specifically, the regression model, with ROA as the dependent variable, suggests that ESG initiatives have a clear negative impact. On the other hand, the variable Tobin's Q increases when ESG increases. This could be explained by the different horizons of the measures and other factors affecting the business environment.
Keywords: 650; ESG initiatives; financial performance; Norwegian listed firms